Define adjoint state
a(t)=āz(t)āLossā(1) From t to t+Ļµ (Ļµ change in time) we have
z(t+Ļµ)=ā«tt+Ļµāf(z(t),t,Īø)āt+z(t)=TĻµā(z(t),t)(2) And because of chain rule ( āxāyā=āuāyāāxāuā )
a(t)=a(t+Ļµ)āz(t)āTĻµā(z(t),t)ā(3) Take the definition of derivative:
ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t)ā(4) Substitue (3) in (4)
ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)āz(t)āTĻµā(z(t),t)āā(5) ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)āz(t)āāTĻµā(z(t),t)ā(6) Taylor series around z(t) in (6)
ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)āz(t)āā(z(t)+Ļµf(z(t),t,Īø)+O(Ļµ2))ā(7) aka TĻµā(z(t),t) to z(t)+Ļµf(z(t),t,Īø)+O(Ļµ2) when limĻµā0ā
aka when Ļµ change in time is small, take range Ļµā0=Ļµ and become Ļµf(z(t),t,Īø), to make up for the loss add O(Ļµ2) at the end (notice it is related to Ļµ)
Expand (7)
ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)(āz(t)āāz(t)+āz(t)āāĻµf(z(t),t,Īø)+O(Ļµ2))ā(8) aka āz(t)āāz(t)=I
ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)(I+āz(t)āāĻµf(z(t),t,Īø)+O(Ļµ2))ā(9) ātāa(t)ā=Ļµā0limāĻµa(t+Ļµ)āa(t+Ļµ)(I+Ļµāz(t)āf(z(t),t,Īø)ā+O(Ļµ2))ā(10) ātāa(t)ā=Ļµā0limāĻµāa(t+Ļµ)Ļµāz(t)āf(z(t),t,Īø)ā+O(Ļµ2)ā(11) aka a(t+Ļµ)āa(t+Ļµ)I=0
ātāa(t)ā=Ļµā0limāāa(t+Ļµ)āz(t)āf(z(t),t,Īø)ā+O(Ļµ)(12) and because limĻµā0ā
ātāa(t)ā=āa(t)āz(t)āf(z(t),t,Īø)ā(13)